Vanitas und Gesellschaft - Benthien, Claudia; Schmidt, Antje; Wobbeler, Christian (De Gruyter, 2021)
This interdisciplinary volume delves into the significance of the early modern vanitas motif in the present day. In the arts, pop culture, and social discourses, it is utilized to make cultural-critical diagnoses. Reflections about the mortality of human life, about decadence and conceit, or the futile pursuit of happiness are updated, but they are joined by new topics such as climate change and transhumanism.